Chimney sweeps : yesterday and today - Giblin, James Cross, 1933-2016.; Tomes, Margot (New York : Crowell, 1982)
Traces the history and folklore of the chimney-sweeping profession from the fifteenth century to the present day, emphasizing the plight of the often abused climbing boys of past centuries.
Includes index.
Bibliography: p. 52-53.
Keywords: Chimney sweeps -- History -- Juvenile literature; Chimney sweeps